INSTITUTIONAL CONDITIONS FOR THE DEVELOPMENT OF AGRICULTURAL BIOGAS PLANTS AS PART OF THE BIOECONOMY SECTOR IN GERMANY - Wojciech Ciechanowski; Mariusz Maciejczak (Annals of the Polish Association of Agricultural and Agribusiness Economists, 2025)
As part of a sustainable economy based on renewable energy sources, the energy sector plays a key role in economic and climate policy. The institutional measures taken in Germany in the bioeconomy and the field of biogas plants and renewable energy development are the primary purpose of this study. The study focused on the regulatory and policy measures taken in Germany to support the development of biogas plants in the country. A literature review on the bioeconomy and agricultural biogas plants was used in the study. An assessment of the measures’ effectiveness was made, and potential applications for other countries wishing to develop the area of electricity production from biogas were identified. The results show that the German government’s measures contributed to increased renewable energy sources and the country’s electricity production balance. At the same time, there is a notable slowdown in energy development produced by biogas plants. Agricultural biogas plants are an essential foundation for the energy transition. Germany’s experience shows that the development of biogas plants requires long-term support strategies and the efficient use of biomass. Further research should focus on the effectiveness of support mechanisms for existing and newly established biogas plants. Upcoming studies could also include the search for innovative financing models to encourage private and public investment, thereby supporting the sustainable development of the agricultural biogas sector.